KiDS-450: enhancing cosmic shear with clipping transformations. Issue 4 (18th August 2018) - Giblin, Benjamin; Heymans, Catherine; Harnois-Déraps, Joachim; Simpson, Fergus; Dietrich, Jörg P; Van Waerbeke, Ludovic; Amon, Alexandra; Asgari, Marika; Erben, Thomas; Hildebrandt, Hendrik; Joachimi, Benjamin; Kuijken, Konrad; et al.
ABSTRACT: We present the first 'clipped' cosmic shear measurement using data from the Kilo-Degree Survey (KiDS-450). 'Clipping' transformations suppress the signal from the highest density, non-linear regions of cosmological fields. We demonstrate that these transformations improve constraints on S 8 = σ8 (Ωm /0.3) 0.5 when used in combination with conventional two-point statistics. For the KiDS-450 data, we find that the combined measurements improve the constraints on S 8 by 17 per cent, compared to shear correlation functions alone. We determine the expectation value of the clipped shear correlation function using a suite of numerical simulations, and develop methodology to mitigate the impact of masking and shot noise. Future improvements in numerical simulations and mass reconstruction methodology will permit the precise calibration of clipped cosmic shear statistics such that clipping can become a standard tool in weak-lensing analyses.